70 HYPERPARATHYROIDISM AND THE CALCIUM PARADOX OF ALDOSTERONISM. (1st January 2005) - Chhokar, V. S.; Sun, Y.; Bhattacharya, S. K.; Ahokas, R. A.; Myers, L. K.; Xing, Z.; Smith, R. A.; Gerling, I. C.; Weber, K. T.
Abstract : Purpose: In congestive heart failure (CHF), aldosteronism may induce a syndrome that features oxi/nitrosative stress, a proinflammatory phenotype, soft tissue and bone wasting. We hypothesized aldosterone/1% NaCl treatment (ALDOST) in rats enhances urinary and fecal Ca2+ and Mg2+ excretion and leads to systemic effects, including secondary hyperparathyroidism (SHPT). Methods: At 1, 2, 4 and 6 weeks of ALDOST we monitored Ca2+ and Mg2+ excretion; ionized [Ca2+]o and [Mg2+]o, parathyroid hormone (PTH) and α1-antiproteinase activity (α1-AP) in plasma; bone mineral density (BMD) and bone strength (BS); total intracellular Ca2+ and Mg2+ in peripheral blood mononuclear cells (PBMC) and ventricular tissue; lymphocyte H2O2 production; and NADPH oxidase activation in ventricular tissue. A separate group received spironolactone (Spi), an aldosterone receptor antagonist. Age-/gender-matched unoperated and untreated rats served as controls. Results: ALDOST induced a marked (p < .05) and persistent rise (3-5 fold) in both 24 hour urinary and fecal Ca2+ and Mg2+ excretion at weeks 1-6, together with progressive reductions (p < .05) in plasma [Ca2+]o and [Mg2+]o, and elevation (p < .05) in PTH. A fall (P < .05) in BMD and BS was seen at weeks 4 and 6. An early, sustained increase (p < .05) in PBMC Ca2+ and Mg2+ and increase (p < .05) in ventricular tissue Ca2+ was seen at weeks 4 and 6 Plasma α1-AP activity was reduced (p < .05) while lymphocyte H2O2 production was increased (p < .05) at all time points and gp91phox-positive inflammatory cells invaded the perivascular space of intramural coronary arteries of both ventricles at weeks 4 and 6. Spi co-treatment attenuated (p < .05) urinary and fecal Ca2+ and Mg2+ excretion, prevented the fall in [Ca2+]o and [Mg2+]o, rescued BMD and BS, and prevented Ca2+ loading of PBMC and cardiomyocytes. Conclusions: Aldosteronism promotes urinary and fecal Ca2+ and Mg2+ excretion leading to a fall in plasma ionized [Ca2+]o and [Mg2+]o with SHPT and bone resorption. PTH-mediated Ca2+ loading of PBMC and cardiac tissue induces oxi/nitrosative stress and results in a proinflammatory phenotype. SHPT accounts for this Ca2+ paradox and contributes to the pathophysiology of CHF with aldosteronism. This work was supported, in part, by NIH Training Grant GR HL07641 (to V.S.C.).